Narratives of negligence : on the accusations of negligence in relation to Iceland's 2008 banking collapse - Sigurjón Arnórsson 1987- (2011)
This assignment will collect statements from multiple sources which have either been accused of or have accused others of negligence in relation to the 2008 banking collapse in Iceland. These statements will be analyzed and recorded in the format of a third person objective narrative. Althingi´s Special Investigation Commission delivered a report on the 2008 collapse of the Icelandic banking sector on April 12, 2010. In this report the Special Investigation Commission accuses leading figures of Iceland‟s former government of being guilty of negligence. These accusations have been disputed by the accused and were considered by the current Icelandic parliament which voted 33-30 in favor of bringing charges against ex- Prime Minister Geir Haarde in the Landsdomur court for negligence in relation to his role in Iceland‟s 2008 financial crash. With their protests over accusations of negligence, leading figures of Iceland‟s former government have also accused a variety of influential people for being negligent, including former employees of the central bank and Iceland‟s commercial banks. From this discourse it has also been suggested that Iceland‟s 2008 financial crash is related to a negligent culture driven by greed. According to some this negative culture has existed in Iceland since the 1990‟s. This assignment aims to organize these competing accusations of negligence into one coherent narrative.